The judgment - Lewis, Beverly, 1949- (Minneapolis, Minn. : Bethany House, 2011)
Rose Kauffman is engaged to Silas Good, a well-liked Amish fellow, so why does she still pine for Nick Franco, the former foster son of the bishop? Meanwhile, Rose's older sister, Hen, has returned to live at her parents' farm with her young daughter. Hen and her modern husband, Brandon, are separated by mutual agreement, although he is threatening to sue for custody of their daughter if Hen does not return soon.
Keywords: Amish -- Fiction; Pennsylvania Dutch Country (Pa.) -- Fiction